Winter operation of the slotted floor, open-front, finishing building - C K Spillman (Kansas Agricultural Experiment Station Research Reports, 1973)
Interest in environmentally-controlled facilities for swine has been increasing recently. Farrowing in such a facility can be justified for producers who plan to be producing pork for some time. However, many producers, with good justification, prefer open-front buildings for finishing pigs. The growing and finishing unit at the Kansas Agricultural Experiment Station is an open-front building facing south, with all pen floors slotted and a liquid-manure, oxidation ditch beneath. It is two wings connected by a storage and service area. Each wing is a metal-sided, clear-span structure containing 16 pens, 6 x 15 ft with a 6 ft alley on the south side. The roof is insulated with an exposed, one-inch blanket faced with a plastic vapor barrier: outside walls have sprayed-on insulation approximately one inch thick.; Swine Day, Manhattan, KS, November, 1973
Keywords: Swine day; 1973; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 203; Swine; Finishing building; Farrowing; Insulation